Energy-saving measurement system and method - EGNOR TERRY; REICHMUTH HOWARD; CAMPBELL WILLIAM C (2016)
The invention relate to an energy-saving measurement system and a method. The system comprises: an energy load measuring instrument which is suitable for independently or universally measuring total energy load of a facility, a data recorder indicating data of external environment temperature measured on a heat metering instrument during a first time period, the heat metering instrument being suitable for measuring temperature of external environment which is close to the facility and generating data indicating the external environment temperature during the first time period, and a data processing circuit which processes the data indicating the total energy load of the measured facility during the first time period and the measured data indicating external environment temperature during the first time period, and depolymerizes usage energy load parts used by a plurality of identification terminals from the measured total energy load of the facility, and generates a first simulation facility model including t